Pengaruh Pelaksanaan Standar Mutu Pendidikan terhadap Kinerja Guru di Pondok Pesantren Bahrul Ulum - Rahman, Zikri (Lembaga Anotero Scientific, 2022)
The Influence of Implementing Education Quality Standards on Teacher Performance at the Bahrul Ulum Islamic Boarding School. This research examines the Influence of Education Quality Standards Implementation on Teacher Performance at the Bahrul Ulum Islamic Boarding School. The formulation of the research problem is: 1) Is there an influence of the implementation of educational quality standards on teacher performance at the Bahrul Ulum Islamic Boarding School Tsanawiyah Madrasah? 2) How does the implementation of educational quality standards affect teacher performance at the Bahrul 'Ulum Islamic Boarding School? This research is field research, namely research carried out directly in the field to obtain the required data. The type of research that the author uses is quantitative research which uses data collection methods using questionnaires, while data analysis uses simple linear regression analysis. The results of this research show that: 1) there is an influence between the Implementation of Education Quality Standards and Teacher Performance, seen from the calculated t value of 7.113 > t table (1.671); 2) the magnitude of the influence caused by the Implementation of Education Quality Standards on Teacher Performance can be determined by looking at the R Square Model Summary table. The R2 (R Square) figure is 0.522 or (52.2%) the magnitude of the influence of the implementation of Education Quality Standards on Teacher Performance and the rest around 47.8% is influenced by other variables.